An update on ocular allergy. Issue 5 (October 2016) - Shaker, Marcus; Salcone, Erin
Abstract : Purpose of review: The update reviews prevalence, classification, cause, and treatment options for allergic eye disease. Recent findings: The incidence of allergic eye disease is underreported but may affect almost all patients with allergic rhinitis. Increased rates of oculonasal symptoms have been reported in the United States resulting in significant economic expenditures. The spectrum of allergic conjunctivitis and its differential considerations include seasonal and perennial conjunctivitis, vernal and atopic keratoconjunctivitis, and giant papillary conjunctivitis. Patients with allergic conjunctivitis have classic immunoglobulin E-mediated pathophysiology and treatments directed at allergen avoidance, traditional pharmacotherapy with oral antihistamines, topical dual-acting antihistamine/mast cell stabilizer agents, and treatment of tear film dysfunction are first-line management strategies. Immunotherapy is an effective treatment option and refractory cases may require ophthalmology comanagement for consideration of topical ester-based corticosteroid therapy and consideration of topical immunomodulators. Summary: Ocular allergy involving specific modifiable and treatable environmental sensitizations is common and often underrecognized. It can impair quality of life to varying degrees. Some cases are quite refractory to management and may require multidisciplinary coordination of care between allergy and ophthalmology specialists. Understanding classification, triggers, and treatment options is important in designing the most appropriate patient-tailored management plans.